2014
DOI: 10.1016/j.vaccine.2014.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of an adenoviral-based Middle East Respiratory Syndrome coronavirus vaccine in BALB/c mice

Abstract: A new type of coronavirus has been identified as the causative agent underlying Middle East Respiratory Syndrome (MERS). The MERS coronavirus (MERS-CoV) has spread in the Middle East, but cases originating in the Middle East have also occurred in the European Union and the USA. Eight hundred and thirty-seven cases of MERS-CoV infection have been confirmed to date, including 291 deaths. MERS-CoV has infected dromedary camel populations in the Middle East at high rates, representing an immediate source of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 52 publications
1
146
0
3
Order By: Relevance
“…A DNA vaccine, which was developed by expressing the synthetic consensus anti-spike protein has shown immunogenicity in mice, nonhuman primates (NHPs) and camels (Muthumani et al, 2015), and another DNA plasmid vaccine that expresses the MERS-CoV S glycoprotein has entered Phase I clinical trials (Clinical Trials.gov, 2016). Additionally, delivery of the S antigen by way of DNA vaccination, nanoparticles, recombinant viral vectors such as modified vaccinia Ankara or adenovirus or RBD-based subunit vaccines have shown immunogenicity and efficacy in mice and/or NHPs against MERS-CoV challenge (Du et al, 2013b;Muthumani et al, 2015;Wang et al, 2015;Coleman et al, 2014;Song et al, 2013;Volz et al, 2015;Kim et al, 2014;Lan et al, 2014Lan et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A DNA vaccine, which was developed by expressing the synthetic consensus anti-spike protein has shown immunogenicity in mice, nonhuman primates (NHPs) and camels (Muthumani et al, 2015), and another DNA plasmid vaccine that expresses the MERS-CoV S glycoprotein has entered Phase I clinical trials (Clinical Trials.gov, 2016). Additionally, delivery of the S antigen by way of DNA vaccination, nanoparticles, recombinant viral vectors such as modified vaccinia Ankara or adenovirus or RBD-based subunit vaccines have shown immunogenicity and efficacy in mice and/or NHPs against MERS-CoV challenge (Du et al, 2013b;Muthumani et al, 2015;Wang et al, 2015;Coleman et al, 2014;Song et al, 2013;Volz et al, 2015;Kim et al, 2014;Lan et al, 2014Lan et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of IgG1 and IgG2a, which were similar for both antigens, increased over time and then were boosted to their peak level as they plateaued for 3 weeks postboost. Similarly, the nAb levels doubled after the boost, and they plateaued for 3 weeks . The second group used an Ad41 vector, derived from Ad41 virus that infects humans naturally via the gastrointestinal route, making it a suitable vector to induce mucosal immunity and to allow for oral immunization.…”
Section: Current Mers‐cov Vaccine Candidates Under Developmentmentioning
confidence: 99%
“…Reports have indicated that recombinant Ad5 vectors, which encode the full-length or S1 extracellular domain, of MERS-CoV S protein induced MERS-CoV S-specific antibody responses in immunized mice, neutralizing MERS-CoV infection in vitro [14]. Ad5 or Ad41 vectors expressing full-length S protein of MERS-CoV have elicited MERS-CoV-specific antibody responses, neutralizing antibodies and T-cell responses in immunized mice [15].…”
Section: Current Status Of Mers Vaccinesmentioning
confidence: 99%